2008
DOI: 10.1002/mds.22002
|View full text |Cite
|
Sign up to set email alerts
|

Regression of symptoms after selective iron chelation therapy in a case of neurodegeneration with brain iron accumulation

Abstract: We report the results of iron chelating treatment with deferiprone in a 61-year-old woman with signs and symptoms of neurodegeneration with brain iron accumulation (NBIA). After 6 months of therapy the patient's gait had improved and a reduction in the incidence of choreic dyskinesias was observed. Her gait returned to normal after an additional 2 months of therapy, at which time there was a further reduction in involuntary movements and a partial resolution of the blepharospasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 11 publications
1
50
0
Order By: Relevance
“…4 An individual case report 5 and a separate pilot phase II study by Zorzi et al 6 have suggested that deferiprone is safe, well-tolerated and effective in lowering iron levels in brain as measured by MRI; conclusions also supported by the current study. Clinical benefit, however, is less clear from these combined data.…”
supporting
confidence: 73%
“…4 An individual case report 5 and a separate pilot phase II study by Zorzi et al 6 have suggested that deferiprone is safe, well-tolerated and effective in lowering iron levels in brain as measured by MRI; conclusions also supported by the current study. Clinical benefit, however, is less clear from these combined data.…”
supporting
confidence: 73%
“…12 One case of putative NBIA was treated successfully at our center, resulting in the disappearance of choreic dyskinesias and the normalization of gait disturbances. 13 Deferiprone, despite its possible side effects (gastrointestinal disturbances, transient increase of transaminases, and, especial- Inclusion criteria were: patients over 18 years of age with neurological symptoms correlated with iron deposition in the basal ganglia as documented by MRI (T2* and T2 signal decrease in the basal ganglia), performed within six months of enrolment. Exclusion criteria were: inability to undergo MRI; renal insufficiency (creatinine >1.5 mg/dL); neoplasias, systemic cardiovascular, severe renal and hepatic diseases; known hypersensitivity to deferiprone; pregnancy and breastfeeding.…”
Section: Introductionmentioning
confidence: 99%
“…This has important clinical implications because clinical trials are currently underway for deferiprone, a chelating agent known to traverse the blood-brain barrier. 15 Deferiprone has been shown to reverse iron deposition in Friedreich ataxia, associated with an appreciable decrease in iron content as measured by MR imaging. 12 It remains to be seen whether this agent will have a similar effect in NBIA and whether decreasing the brain iron burden will affect patients' clinical courses.…”
mentioning
confidence: 99%